2022
DOI: 10.1039/d2mh00135g
|View full text |Cite
|
Sign up to set email alerts
|

Multi-compartment supracapsules made from nano-containers towards programmable release

Abstract: The assembly of nanomaterials into suprastructures offers the possibility to fabricate larger scale functional materials, whose inner structure strongly influences their functionality for a vast range of applications. In spite...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
8
0
2
Order By: Relevance
“…This was inseparable from the interaction between lignin, [36][37][38][39] and these multi-order interactions resulted in the aggregation of composite colloidal particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was inseparable from the interaction between lignin, [36][37][38][39] and these multi-order interactions resulted in the aggregation of composite colloidal particles.…”
Section: Resultsmentioning
confidence: 99%
“…According to the particle size test, the particle size of the four groups of samples in water increased with increasing lignin grafting amount, indicating that magnetic composite colloidal particles formed aggregates in water. This was inseparable from the interaction between lignin, [ 36–39 ] and these multi‐order interactions resulted in the aggregation of composite colloidal particles.…”
Section: Resultsmentioning
confidence: 99%
“…They employed a microfluidic cross‐junction to form oil droplets containing dextran‐based nanogels, which spontaneously assemble into supraparticles when evaporating the solvent. The group showed that the van‐der‐Waals forces responsible for holding the nano‐compartments together can be broken by a high‐energy input in form of ultrasonication, causing the supraparticles to separate into singular entities again [29] . While these compartmentalized supracapsules allow for the transport and release of multiple drug payloads, it remains challenging to integrate cargoes exhibiting opposing physicochemical properties or charges.…”
Section: Introductionmentioning
confidence: 99%
“…Auf diese Weise ließen sich die Suprapartikel wieder in ihre einzelnen Einheiten zerlegen. [29] Obwohl die kompartimentären Suprakapseln den simultanen Transport mehrerer Wirkstoffe ermöglichen, bleibt es eine Herausforderung, Frachtmoleküle mit unterschiedlichen physikalischchemischen Eigenschaften oder gegensätzlichen Ladungen zu integrieren.…”
Section: Introductionunclassified
“…Die Gruppe konnte zudem demonstrieren, dass die Van‐der‐Waals‐Kräfte, die für den Zusammenhalt der Nanokompartimente verantwortlich sind, durch einen hohen Energieeintrag in Form von Ultraschall aufgehoben werden können. Auf diese Weise ließen sich die Suprapartikel wieder in ihre einzelnen Einheiten zerlegen [29] . Obwohl die kompartimentären Suprakapseln den simultanen Transport mehrerer Wirkstoffe ermöglichen, bleibt es eine Herausforderung, Frachtmoleküle mit unterschiedlichen physikalisch‐chemischen Eigenschaften oder gegensätzlichen Ladungen zu integrieren.…”
Section: Introductionunclassified